Hot-dogging : a guide to stunt skiing - Johnson, Rob. (Philadelphia, Pennsylvania : Dorrance & Company, 1974)
This book is concerned with creativity and morale on the ski slopes, and it is meant to be a force for bringing change to the most dynamic and exciting winter sport. It is not intended for the novice or first-time skier, and many of the stunts which are demonstrated should not be attempted by any but the most athletic and talented skier.
Exercise and safety -- Equipment -- Stunts.
Keywords: SKIING